Endosomal Escape: Amphiphilic Polyelectrolyte Graft Copolymers Enhance the Activity of Cyclic Dinucleotide STING Agonists (Adv. Healthcare Mater. 2/2021). Issue 2 (20th January 2021) - Nguyen, Dinh Chuong; Shae, Daniel; Pagendarm, Hayden M.; Becker, Kyle W.; Wehbe, Mohamed; Kilchrist, Kameron V.; Pastora, Lucinda E.; Palmer, Christian R.; Seber, Pedro; Christov, Plamen P.; Duvall, Craig L.; Wilson, John T.
Abstract : Endosomal escape is a rate limiting step for many promising therapeutics, including cyclic dinucleotide (CDN) agonists of the stimulator of interferon genes (STING) pathway. In article number 2001056, John T. Wilson and co‐workers synthesize and screen a novel library of polymers with pH‐responsive, membrane‐destabilizing activity and evaluate their capacity to enhance cytosolic delivery of CDNs, resulting in identification of new drug carrier technologies for potent STING activation.